2014
DOI: 10.4161/gmic.29797
|View full text |Cite
|
Sign up to set email alerts
|

A commensal bacterial product elicits and modulates migratory capacity of CD39+CD4 T regulatory subsets in the suppression of neuroinflammation

Abstract: Tolerance established by host-commensal interactions regulates host immunity at both local mucosal and systemic levels. The intestinal commensal strain Bacteroides fragilis elicits immune tolerance, at least in part, via the expression capsular polysaccharide A (PSA). How such niche-specific commensal microbial elements regulate extra-intestinal immune responses, as in the brain, remains largely unknown. We have recently shown that oral treatment with PSA suppresses neuro-inflammation elicited during experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 51 publications
3
76
0
Order By: Relevance
“…3D). Interestingly, tumor-infiltrating CD39 C gdT cells rendered much greater immunosuppressive property than other immunosuppressive T cells, including CD39 C CD4 C20, 21 and CD39 C CD8 C T cells 18,22,23 (Fig. 3C and D).…”
Section: Tumor-infiltrating Cd39 C Gdt Cells Have Potent Immunosupprementioning
confidence: 99%
“…3D). Interestingly, tumor-infiltrating CD39 C gdT cells rendered much greater immunosuppressive property than other immunosuppressive T cells, including CD39 C CD4 C20, 21 and CD39 C CD8 C T cells 18,22,23 (Fig. 3C and D).…”
Section: Tumor-infiltrating Cd39 C Gdt Cells Have Potent Immunosupprementioning
confidence: 99%
“…Although genetic susceptibility is a factor that may determine disease, other risk factors are also necessary, in particular, environmental triggers such as those associated with known risk factors. We, among other investigators, explored the effects of the gut microbiota in experimental autoimmune encephalomyelitis (EAE) models of MS and proposed the idea that the composition of the gut microbiota is relevant for the balance of the proinflammatory and anti-inflammatory cell subpopulations that result in disease induction or protection [9][10][11][12][13][14][15][16][17]. This special issue covers the most recent literature on the experimental models and the clinical evidence for changes in the gut microbiota observed in patients with MS. Tremlett and Waubant [18] explore the microbiota of pediatric MS cases.…”
mentioning
confidence: 99%
“…Our laboratory has previously shown that oral treatment with PSA protects mice against EAE through the induction of regulatory CD39 + T cells and Foxp3 + T regulatory cells (Tregs) (24,26,27). B. fragilis colonization also improves the integrity of the barrier (9).…”
mentioning
confidence: 99%
“…Furthermore, treatment with oral antibiotics also reduce significantly the severity of EAE (30,31). The experimental evidence gathered using animal model studies indicate the effects of the microbiota in the regulation of EAE in animals (24,(26)(27)(28)(32)(33)(34)(35)(36). Furthermore, gut microbes, such as B. fragilis and Lactobacillus rhamnosus have been shown to interact with neurons in the enteric nervous system (ENS) directly and affect their function (37).…”
mentioning
confidence: 99%